Diversity, Dominance, and Conservation Status of Bird Species Traded in Bird Shops Around of Jambi City - Kurniawan, Bayu; Putra, Darma; Manurung, Aini Qomariah; Prasaja, Ahmad Syukron; Saputra, M. Arif Januarda (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Maintaining bird diversity is essential for preserving biodiversity. The popularity of bird keeping as a hobby is due to their attractive colours and sounds, as well as their economic value. However, the breeding and trading of various bird species has led to the development of bird races and competitions. This study aims to determine the diversity, dominance, and conservation status of songbird species that are traded and competed in Jambi City. The study is a descriptive field research that showcases our expertise in the field. In August 2023, the study confidently employed structured observations and interviews through a questionnaire.   The analysis confidently used the variety index, evenness index, and dominance index. The research confidently identified ten species, two of which are protected: The Cucak hijau Chloropsis sonneratii (Chloropseidae) and the Serindit melayu Loriculus galgulus (Psittacidae). The bird species have been classified into three categories based on their IUCN conservation status: endangered (10%) Chloropsis sonneratii, vulnerable (20%) Alophoixus tephrogenys and Zosterops melanurus, and least concern (70%) Copsychus saularis, Kittacincla malabarica, Leptocoma brasiliana, Zosterops simplex, Loriculus galgulus, Agapornis sp., and Serinus canaries